DAMPAK SERTIFIKASI TERHADAP KINERJA MENGAJAR GURU DI MADRASAH ALIYAH NEGERI (MAN) 1 KOTA BOGOR - Aprilia, Indri; Sobari, Ahmad (FIKRAH, 2018)
This Paper Intends to know The Impact Certification to Performance Teaching Teachers of Madrasah Aliyah Negeri (MAN) 1 Bogor City. Covers Process Performance Teaching Teachers In Learning Planning, Implementation of Learning and Evaluation of Learning. This Research used the Qualitative Approach by Describes The Data That in Earn through Words Or sentence that in separate to Earn Conclusion. The Location of the Research is Madrasah Aliyah Negeri (MAN) 1 Bogor City is Located on Jalan Dr. Semeru Komp. Bumi Menteng Asri Bogor Barat. Data Source in this research are Teacher Certification, Teacher not been Certified, Parts of The Curriculum and Students. Data Obtained by Interview, Observation and Documentation. Data was Analysed by three activity, that are Reducing, Presentation, and Conclusion. According to The Result of Data Analysis Indicate that Performance Teaching Teachers in Madrasah Aliyah Negeri (MAN) 1 Bogor City is Good Enough. However still there is Teacher that can not adjust him as Professional Teachers that to be responsible to Teaching Performance tasks And existence Positive Impact that Significant in Certification Program to Performance Teaching Teachers of Madrasah Aliyah Negeri (MAN) 1 Bogor City.